The figure of the taṇḍa in old Javanese literary and epigraphical records - Jákl, Jiří (Bijdragen tot de taal-, land- en volkenkunde, 2019)
Abstract: This article offers a detailed analysis of the category of men known as taṇḍa. Widely attested in literary records and known from Old Javanese inscriptions, the function and social status of taṇḍa has been a controversial issue. Two views pertaining to the identity of these men have been advanced so far. According to most scholars, taṇḍa were high-status officials, often interpreted as military ‘officers’. According to an alternative view, they were low-status military figures and their function was to oversee markets, or they were low-status figures associated with music and performances. This article argues that until at least 1200 CE taṇḍa were court-based, active combatants, who had troops of their own followers at their disposal and were responsible for the military expansion of Javanese states. By the Majapahit period they were integrated as regular troops into the progressively more hierarchical system of the professional standing army, which resulted in their reduced social status.
Gesehen am 21.01.2020